2018
DOI: 10.1097/aap.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Anxiety and Depression Are Mediated by Changes in Pain Severity in Patients Undergoing Lower-Extremity Total Joint Arthroplasty

Abstract: Presurgical affective symptoms not only have an effect on change in postsurgical pain, whereby lower preoperative scores on depression and anxiety were associated with lower postsurgical pain, but also postsurgical decreases in pain were associated with lower levels of depression and anxiety after surgery. Taking these points into consideration may prove useful in working toward better outcomes for TJA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…In a systematic review, post-operative pain was reported in 9% of patients after THA in the follow-up [31]. Improvements in pain and physical function after lower extremity total joint arthroplasty were associated with improvement in depression and anxiety symptoms [32]. After having had an acute pain experience, some patients are unable to resume their daily levels of activity and tend to regard pain as a threat [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review, post-operative pain was reported in 9% of patients after THA in the follow-up [31]. Improvements in pain and physical function after lower extremity total joint arthroplasty were associated with improvement in depression and anxiety symptoms [32]. After having had an acute pain experience, some patients are unable to resume their daily levels of activity and tend to regard pain as a threat [33].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain after TKA can affect all dimensions of health-related quality of life, and has been found to be associated with functional limitations, depression, anxiety, poorer general health, sleep problems and long-term opioid use. 28 - 32 Older people with chronic pain after joint arthroplasty can experience interference with relationships and become socially isolated, which is a risk factor for other problems and can limit their capacity to bring about change or to seek help for their pain. 31 , 33 , 34 Some people experience considerable pain-related distress, and this is often highest in those who experience no change or deterioration in pain symptoms following surgery.…”
Section: Personal and Economic Impactmentioning
confidence: 99%
“…However, it is difficult to establish a clear relationship between any one of these variables. Prospectively collected data following total knee and hip arthroplasty found that improvements in pain and physical function were associated with improvements in anxiety and depression 6 months after surgery, and the change in overall body pain mediated these changes in affect 35. Unfortunately, our study was underpowered to detect mediating factors such as overall body pain that may play a role.…”
Section: Discussionmentioning
confidence: 86%